ENTREPRENEURIAL MOTIVATION AND ITS IMPACT ON MOMPRENEUR BUSINESS PERFORMANCE (STUDY ON SONGKET AND BATIK WOMEN ENTREPRENEURS IN JAMBI CITY) - Erwita Dewi (JOURNAL OF BUSINESS STUDIES AND MANGEMENT REVIEW, 2022)
Women entrepreneurs have become a rapidly growing phenomenon in the last decade. In the province of Jambi, the development of the MSME sector has also continued to increase, as has the case in the city of Jambi. Female MSMEs are dominated by housewives and those who already have children are also known as "Mompreneurs". The motivation of women entrepreneurs to enter into the world of business or to become entrepreneurs is not only because of business activities that might be in accordance with their hobbies but also because of the family's economic conditions which require them to be able to find additional income.This research is an empirical study by examining the impact of Mompreneur entrepreneurial motivation on business performance.